Bankruptcy Boedel Execution Practices in Indonesia (Journal of Private and Commercial Law, 2020)
The ASEAN economic community is one of the pillars of the agreement to form ASEAN. As the integrated economic identity of Southeast Asia, MEA aims to create a single market and production base marked by the free flow of goods, services and investment. A bankruptcy issue crosses national borders arises, when debtors in Indonesia have bankrupt assets abroad. Where the bankruptcy execution process is hampered by existing rules in the country itself, especially in ASEAN, one of the international organizations in the regional level which is one of Indonesia's members, does not yet have regulations that bind its members to the problem of bankruptcy boedel. 1967 UN model law "UNCITRAL cross border insolvency" which aims to be a reference for the resolution of the bankruptcy bankruptcy problem in ASEAN. In my opinion, UNCITRAL is a flexible legal product and can be used as a harmonization of bankruptcy law in ASEAN.